Altered sensorimotor integration in multiple sclerosis: A combined neurophysiological and functional MRI study. Issue 9 (September 2021) - Giannì, C.; Belvisi, D.; Conte, A.; Tommasin, S.; Cortese, A.; Petsas, N.; Baione, V.; Tartaglia, M.; Millefiorini, E.; Berardelli, A.; Pantano, P.
Highlights: Upper limb sensorimotor integration is altered in multiple sclerosis and contributes to upper limb movement velocity reduction. Thalamic functional connectivity with brain areas of sensorimotor circuit correlates with upper limb sensorimotor integration. High intrathalamic synchronization and low thalamic synchronization with sensorimotor cortex correlate to better motor performance. Abstract: Objective: To explore whether abnormal thalamic resting-state functional connectivity (rsFC) contributes to altered sensorimotor integration and hand dexterity impairment in multiple sclerosis (MS). Methods: To evaluate sensorimotor integration, we recorded kinematic features of index finger abductions during somatosensory temporal discrimination threshold (STDT) testing in 36 patients with relapsing-remitting MS and 39 healthy controls (HC). Participants underwent a multimodal 3T structural and functional MRI protocol. Results: Patients had lower index finger abduction velocity during STDT testing compared to HC. Thalamic rsFC with the precentral and postcentral gyri, supplementary motor area (SMA), insula, and basal ganglia was higher in patients than HC. Intrathalamic rsFC and thalamic rsFC with caudate and insula bilaterally was lower in patients than HC. Finger movement velocity positively correlated with intrathalamic rsFC and negatively correlated with thalamic rsFC with the precentral and postcentral gyri, SMA, and putamen. Conclusions: Abnormal thalamic rsFC is a possible substrate for altered sensorimotor integration in MS, with high intrathalamic rsFC facilitating finger movements and increased thalamic rsFC with the basal ganglia and sensorimotor cortex contributing to motor performance deterioration. Significance: The combined study of thalamic functional connectivity and upper limb sensorimotor integration may be useful in identifying patients who can benefit from early rehabilitation to prevent upper limb motor impairment.